Management strategy in patient with familial gigantiform cementoma: A case report and analysis of the literature. Issue 50 (December 2017) - Wang, Hong-Wei; Ma, Chun-Yue; Qin, Xing-Jun; Zhang, Chen-Ping
Abstract: Rationale: Familial gigantiform cementoma (FGC) is a rare benign autosomal dominant fibrocemento-osseous lesion generally limited to the facial bones, typically in the anterior portion of the mandible; it is often associated with abnormalities of the long bones and prepubertal pathologic fractures. Owing to the small number of such patients, a uniform treatment criterion has not been established. This paper presents a patient with FGC who was treated in our department, and offers a systematic review of the patients reported in the literature. Our aim was to explore the treatment strategy for patients with FGC. Patient concerns: Our patient, a 13-year-old boy, presented with a painless enlargement of the mandible first noted 2 years earlier. It had grown rapidly over the preceding 8 months, affecting both his appearance and ability to chew. Diagnosis: Based on the pathologic, clinical, and radiographic features, FGC was diagnosed. Interventions: Mandibuloectomy was performed. The mandibular defect was immediately reconstructed with his right vascularized iliac crest flap. At the same time, a PubMed search was conducted to identify studies reporting on other patients with FGC. Outcomes: A 3-dimensional computed tomography (3D-CT) scan demonstrated appropriate height of the new alveolar bone. Follow-up results showed recovery of the patient's appearance and mandibular function. He was free of recurrence at 4-year follow-up. Lessons: FGC is a rare benign fibrocemento-osseous lesion of the jaws that can cause severe facial deformity. Incomplete removal leads to more rapid growth of the residual lesion. Therefore, extensive resection is a suitable strategy to avoid recurrence. Defects of the facial bones found intraoperatively should be repaired with resort to an appropriate donor site. However, it is important to be aware that patients with FGC always have concomitant abnormalities of skeletal metabolism and structure, as well as a vulnerability to fractures of the long bones of the lower extremity. Therefore, the optimal management strategy should include a review of treatment options for other patients as reported in the literature. An optimal protocol can not only provide sufficient high-quality bone suitable for the reconstruction of bone defects, but also minimize complications and maximize quality of life.